La atracción del abismo colectivo. Georg Simmel, inquisidor de la forma social del conflicto: claves de lectura para comprender el fútbol. - Gaytán Alcalá, Felipe; Bombela Frias, Eduardo Javier (Hermenéutica, 2025)
Football is a mass sport, analyzed from different disciplinary perspectives, some emphasizing collective effervescence, others as part of the process of civilization, and others as a capitalist expression of the alienation of the people. However, football reveals itself as a social form that opens the opportunity to understand modernity through the contrast between individualism and group belonging and indifference to emotionality. This text offers various sociological keys from Georg Simmel's relational perspective to understand this sport as a form of socialization. This allows for an analysis of the dual unity between individuals and society based on emotionality and rationality, indifference, and belonging. How can we approach football to interpret modern society? Although Simmel did not write about football, he does provide an interpretive framework that anchors modernity in the metropolis (indifference and blasé of the street) to compare what soccer contrasts (emotionality and stadium) and all that this implies, as explained in the text. The theoretical and methodological reflection focuses on a conceptual comparison of two forms of socialization: the Blasé of the city and the form of pure conflict in football in the stadium, which spills over into other spaces and times, generating a social geometry of closeness and distance, individuals and groups.